Trimetazidine in coronary heart disease patients: mechanism of action and controlled trials’ results - L. V. Kremneva; O. V. Abaturova; S. V. Shalaev (Кардиоваскулярная терапия и профилактика)
Metabolic cardioprotection is an important part of treating patients with coronary heart disease (CHD). The most widely used drug in this group is trimetazidine. Its mechanism of action is based on fatty acids metabolism inhibition, glucose oxidation activation, intracellular ATP deficit prevention. Numerous randomized, controlled clinical studies demonstrated trimetazidine antiischemic efficacy, similar to that for beta-adrenoblockers or calcium antagonists. Trimetazidine improves myocardial contractility, reduces clinical manifestations of heart failure. The medication beneficially influences ischemia-associated myocardial dysfunction: stunning, hybernation, preconditioning. Trimetazidine is recommended for treating patients with stable angina and ischemic left ventricular dysfunction, in combination with other drugs. Perspectives of trimetazidine therapy in myocardial revascularization and acute myocardial infarction should be examined in future trials.